Delayed Serological Transfusion Reaction After Platelet Transfusion Due to Anti-e - Sachan, Deepti (Indian J Hematol Blood Transfus, 2016)
Delayed serological transfusion reaction (DSTR) is defined as absence of clinical signs of hemolysis and demonstration of new, clinically-significant antibodies against red blood cells after a transfusion, by either positive direct antiglobulin test or positive antibody screen with newly identified RBC alloantibody. Various delayed hemolytic transfusion reaction cases are reported after red cell transfusions. However, the incidence of DSTR after platelet transfusion due to non-Rh(D) antibodies is not much documented. We report here a case of DSTR due to anti-e Rh antibody in a multiply red cell alloimmunized female patient after single donor platelets transfusion.